Exploring Meaningful Learning Experiences Through the Use of Digital Technology in Indonesian Language Learning in Grade IV of Muhammadiyah 1 Elementary School in Surakarta - Adhita Laxmi Sabilla; Harun Joko Prayitno (FKIP - Universitas Riau, 2026)
Learning Indonesian in elementary school requires meaningful learning experiences that enable students not only to understand concepts but also to relate learning materials to real-life contexts. In the digital era, technology offers potential support for meaningful learning practices. This study aims to explore meaningful learning experiences of fourth-grade students through the use of digital technology in Indonesian language learning at SD Muhammadiyah 1 Surakarta. A descriptive qualitative approach with a phenomenological design was employed. Research participants consisted of teachers and fourth-grade students selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and documentation, and analyzed using thematic analysis. The findings indicate that digital technology enhances students’ cognitive and emotional engagement, facilitates understanding of learning materials, and supports the connection between learning content and students’ everyday experiences. Learning activities become more interactive, enjoyable, and relevant, although technical challenges such as unstable internet connections and device differences remain. Overall, digital technology plays an important role in supporting meaningful Indonesian language learning at the elementary school level.